IMPLEMENTASI PEMBELAJARAN MATEMATIKA REALISTIK DALAM MENINGKATKAN HASIL BELAJAR OPERASI PENGURANGAN BILANGAN CACAH - Noor, Nur Alim; Muslimah, Muslimah (Pendidikan Matematika UNIMOR, 2020)
This study aim was to improve the learning results of chopping numbers operation through realistic mathematics learning in one Elementary School at Cipondoh-Tangerang City. This is a Class Action Research according to Kemis model, as many as 3 cycles. The research subjects were 27 students. The results of the study showed that there was an increase in the KKM value. In the first cycle with a student KKM percentage value reaching 52%. The second, increasing in KKM was 69.2%. While the third was 85.2%. The realistic mathematical approach can also improve student learning activities, on the average score of 2.5 or 63% in the first cycle, to 3.0 or 75% in the second cycle, and continues to increase to 3.5 or 87% in the third cycle. Based on the study result, it can be concluded that learning through realistic mathematic learning can improve the mathematics learning results of chopping numbers.